Computational Design of Carbazole-Based D-π-A Sensitizers for High-Performance Dye-Sensitized Solar Cells - Sharma, Kamakshi; Singh, Omna; Singh, Nandini; Guin, Mridula; Singh, N.B. (Asian Journal of Chemistry, 2026)
Dye-sensitized solar cells (DSSCs) are considered as third-generation photovoltaic technology due to single-device architecture, simple fabrication and good performance. Metal-free organic dyes having a donor-π-acceptor (D-π-A) architecture, have attracted major attention of researchers due to the facts that their electrochemical and optical properties can easily be tuned. In this work, two carbazole-based organic dyes, M1 and M2, were computationally designed and tested as potential DSSC sensitizers using density functional theory (DFT) and time-dependent DFT (TD-DFT) methodology. Ground-state geometry optimization at the B3LYP/6-31G(d,p) level which revealed that M1 possesses a more planar molecular structure compared to M2, thereby facilitating enhanced π-conjugation and intramolecular charge transfer. Frontier molecular orbital analysis in both gas and solvent phases revealed that M1 exhibits slightly greater electronic delocalization and excitability compared to M2. Simulated UV-Vis absorption spectra showed strong visible-light absorption, with M1 displaying a red-shifted maximum absorption wavelength (λmax) at 458.81 nm and good light-harvesting capability. Further studies of molecular electrostatic potential (MEP), natural bond orbital (NBO), density of states (DOS), partial density of states (PDOS), reorganization energy and photovoltaic parameters confirmed the favourable charge-transfer characteristics of M1 and M2. Although M2 has lower reorganization energy than M1, the other calculated properties favour M1, which exhibits more favourable optical and electronic characteristics and may be a promising candidate for further experimental evaluation.